2019
DOI: 10.1177/0009922819870557
|View full text |Cite
|
Sign up to set email alerts
|

Breaking a Cycle of Dependence to Improve Neurology Education: A Qualitative Study Exploring Pediatric Residents’ Perspectives

Abstract: Objective. To understand pediatric residents’ experiences and attitudes toward learning neurology; and to identify facilitators and barriers to learning neurology during residency. Study Design. Qualitative study using focus groups of pediatric residents at Stanford during November 2017. Focus groups were audio-recorded and transcribed verbatim. Investigators independently coded the transcripts and reconciled codes to develop themes using constant comparison associated with grounded theory. Results. Eighteen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…In the current study, comfort nursing plus psychological nursing alleviated the anxiety and depression of patients, indicating a promising nursing outcome of this nursing method. Furthermore, this study showed that the total nursing satisfaction of the experimental group after the intervention was significantly higher than that of the control group, which was consistent with the research results of THUY et al [ 23 , 24 ], which revealed that “the nursing satisfaction of the research group (88.24%) was significantly higher than that of 49.02% in the control group,” suggesting that comfort nursing plus psychological care could fulfill the nursing needs of patients, reduce medical disputes, and help create a harmonious nurse-patient relationship. In addition, traditional Chinese medicine care could effectively improve the efficiency of clinical care and the recovery of neurological function of patients, thereby enhancing the quality of life and clinical care of patients.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, comfort nursing plus psychological nursing alleviated the anxiety and depression of patients, indicating a promising nursing outcome of this nursing method. Furthermore, this study showed that the total nursing satisfaction of the experimental group after the intervention was significantly higher than that of the control group, which was consistent with the research results of THUY et al [ 23 , 24 ], which revealed that “the nursing satisfaction of the research group (88.24%) was significantly higher than that of 49.02% in the control group,” suggesting that comfort nursing plus psychological care could fulfill the nursing needs of patients, reduce medical disputes, and help create a harmonious nurse-patient relationship. In addition, traditional Chinese medicine care could effectively improve the efficiency of clinical care and the recovery of neurological function of patients, thereby enhancing the quality of life and clinical care of patients.…”
Section: Discussionsupporting
confidence: 92%